α-Adducin Gly460Trp gene mutation and essential hypertension in a Chinese population: a meta-analysis including 10,960 subjects. - Yan-yan Li (PLoS ONE, 2012)
BACKGROUND: The α-adducin Gly460Trp (G460W) gene polymorphism may be associated with susceptibility to essential hypertension (EH), but this relationship remains controversial. In an attempt to resolve this issue, we conducted a meta-analysis. METHODS: Twenty-three separated studies involving 5939 EH patients and 5021 controls were retrieved and analyzed. Four ethnicities were included: Han, Kazakh, Mongolian, and She. Eighteen studies with 5087 EH patients and 4183 controls were included in the Han subgroup. Three studies with 636 EH patients and 462 controls were included in the Kazakh subgroup. The Mongolian subgroup was represented by only one study with 100 EH patients and 50 controls; similarly, only one study with 116 EH patients and 326 controls was available for the She subgroup. The pooled and ethnic group odds ratios (ORs) along with the corresponding 95% confidence intervals (95% CI) were assessed using a random effects model. RESULTS: There was a significant association between the α-adducin G460W gene polymorphism and EH in the pooled Chinese population under both an allelic genetic model (OR: 1.12, 95% CI: 1.04-1.20, P = 0.002) and a recessive genetic model (OR: 1.40, 95% CI: 1.16-1.70, P = 0.0005). In contrast, no significant association between the α-adducin G460W gene polymorphism and EH was observed in the dominant genetic model (OR: 0.88, 95% CI: 0.72-1.09, P = 0.24). In stratified analysis by ethnicity, significantly increased risk was detected in the Han subgroup under an allelic genetic model (OR: 1.13, 95% CI: 1.04-1.23, P = 0.003) and a recessive genetic model (OR: 1.43, 95% CI: 1.17-1.75, P = 0.0006). CONCLUSIONS: In a Chinese population of mixed ethnicity, the α-adducin G460W gene polymorphism was linked to EH susceptibility, most strongly in Han Chinese.